Human cells lacking coilin and Cajal bodies are proficient in telomerase assembly, trafficking and telomere maintenance - Chen, Yanlian (Nucleic Acids Res, 2015)
The RNA component of human telomerase (hTR) localizes to Cajal bodies, and it has been proposed that Cajal bodies play a role in the assembly of telomerase holoenzyme and telomerase trafficking. Here, the role of Cajal bodies was examined in Human cells deficient of coilin (i.e. coilin-knockout (KO) cells), in which no Cajal bodies are detected. In coilin-KO cells, a normal level of telomerase activity is detected and interactions between core factors of holoenzyme are preserved, indicating that telomerase assembly occurs in the absence of Cajal bodies. Moreover, dispersed hTR aggregates and forms foci specifically during S and G2 phase in coilin-KO cells. Colocalization of these hTR foci with telomeres implies proper telomerase trafficking, independent of Cajal bodies. Therefore, telomerase adds similar numbers of TTAGGG repeats to telomeres in coilin-KO and controls cells. Overexpression of TPP1-OB-fold blocks cell cycle-dependent formation of hTR foci and inhibits telomere extension. These findings suggest that telomerase assembly, trafficking and extension occur with normal efficiency in Cajal bodies deficient human cells. Thus, Cajal bodies, as such, are not essential in these processes, although it remains possible that non-coilin components of Cajal bodies and/or telomere binding proteins (e.g. TPP1) do play roles in telomerase biogenesis and telomere homeostasis.